A Critical Review of Analytical Methods for Determination of Ceftriaxone Sodium. (4th March 2018) - da Trindade, Mariana Teixeira; Salgado, Hérida Regina Nunes
ABSTRACT: Ceftriaxone sodium is a third-generation semi-synthetic antibiotic belonging to the class of cephalosporins. Is administered only by parenteral route and has the ability to cross the blood-brain barrier. It has bactericidal action; its main activity is related to the Gram-negative bacteria, being also able to act against Gram-negative bacilli resistant to the first- and second-generation cephalosporins. The present study presents a survey of the characteristics, properties and analytical methods used for the determination of ceftriaxone sodium, for the gathering of data searches were carried out in scientific articles in the world literature, as well as in the official compendia. It is necessary to create awareness about the importance of developing effective and reliable analytical methods for quality control and consequently for conducting pharmacokinetic, bioavailability, bioequivalence studies as well as for the therapeutic monitoring of this drug. Most of the methods found use high-performance liquid chromatography, but also methods that use absorption spectroscopy ultraviolet, infrared spectroscopy, spectrofluorimetry and microbiological methods have been presented. A discussion was presented highlighting the need to develop new ecological methods using less toxic solvents, rapid analysis and miniaturization of the samples.